Concentration-dependent disturbances of digestive functions in house cricket (Insecta: Orthoptera) exposed to GO-AgNP composite - Reyhaneh Seyed Alian; Barbara Flasz; Andrzej Kędziorski; Magdalena Rost-Roszkowska; Katarzyna Rozpędek; Łukasz Majchrzycki; Maria Augustyniak (Scientific Reports)
Abstract This study investigates the effects of graphene oxide (GO) and silver nanoparticle (AgNP) composite (GO-AgNP) on the digestive physiology and gut ultrastructure of Acheta domesticus (house cricket) during extended exposure. Various concentrations of GO-AgNP were tested to assess their impact on food consumption, assimilation, cell status (Dead Cells and ROS + cells), gut enzyme activity, and structural damage to gut cells. Concentration and exposure time had significant effects on oxidative stress, enzyme activity, and gut cell structure. The applied composite reduced cumulative food consumption and assimilation efficiency. Enzyme assays showed that lower concentrations enhanced carbohydrate-degrading enzyme activity, while higher concentrations inhibited protease activity. Histological analysis revealed structural damage to gut epithelial cells and signs of autophagy or necrosis at higher concentrations. These results suggest that GO and AgNPs contribute to oxidative stress, cell cycle disruption, and apoptosis, with AgNPs having a potentially stronger effect than GO. The disturbed enzyme activity may result from conformational changes caused by nanoparticle agglomeration. These findings underline potential risks associated with the environmental or agricultural use of GO-AgNP composites.